A study on water, sanitation and hygiene practices among the urban slum dwellers of Vellore, Tamil Nadu, India - Chu, Justin Q. Y.; John, Renita; Balasubramanya, Bhavya; Jeyapaul, Shalini; Mohan, Venkata Raghava; John, Ananth; Viola, Chelsea; K., Poornima; Reji, Aashish; John, Sushil; Rebecca, Kajini; ., Lalrintluangi (International Journal Of Community Medicine And Public Health, 2020)
Background: Water, sanitation and hygiene are global concerns for both WHO and UNICEF. The sustainable development goal had targeted improved water sources, but the target of improved sanitation facilities was missed by almost 700 million people worldwide. The less developed and developing nations (like India) did not meet both the targets. Methods: A community-based cross sectional study was conducted in the urban slums of Vellore using the systematic random sampling method. Data was analyzed using frequency and WASH scoring. Further bi-variate and multivariate analyses was done using chi-square test and logistic regression. A total number of 140 households were surveyed using a semi-structured, pilot-tested questionnaire. Results: It was found that 65% of the study population (n=140) had poor wash score (<8). Among the 12 exposure variables analyzed, it was found that three variables had significant association with a poor WASH score (<8), which were: having more than 4 members in a household; living in a kutcha house, and consumption of municipal water. Conclusions: The study showed that the majority of the people dwelling in urban slums in Vellore do not have sufficient knowledge regarding good hygiene practices. A good knowledge regarding proper hygiene practices and the availability of proper facilities is crucial in improving sanitary conditions in the community.